Prevalence of metabolic dysfunction-associated fatty liver disease in kidney transplant recipients: A cross-sectional study using FibroScan - YILMAZ, YUSUF (My University, 2023)
Background and Aim: Metabolic dysfunction-associated fatty liver disease (MAFLD) is expected to be prevalent among kidney transplant recipients (KTRs). In this study, we evaluated the prevalence of MAFLD among KTRs, data that have not been investigated by any clinical study to date. Materials and Methods: We included a total of 52 KTRs and 53 age-, sex-, and BMI-matched individuals as the control group through prospective consecutive recruitment. We detected the presence of hepatic steatosis and liver fibrosis using the controlled attenuation parameter (CAP) and liver stiffness measurement (LSM) defined by FibroScan. Results: Among the KTRs, 18 (34.6%) had metabolic syndrome. The prevalence of MAFLD among the KTRs and controls was 42.3% and 51.9%, respectively (p=0.375). The CAP and LSM values did not differ significantly between the KTRs and controls (p=0.222 and p=0.119). Among the KTRs, patients with MAFLD had significantly higher age, p=0.011, p=0.033, p=0.022, and p=0.029, respectively). In multivariable analysis, age was the only independent factor for MAFLD among the KTRs (OR: 1.120, 95% confidence interval (CI): 1.039-1.208). Conclusion: MAFLD among KTRs did not show a significantly higher with larger populations are needed.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; GASTROENTEROLOJİ VE HEPATOLOJİ; Klinik Tıp; Klinik Tıp (MED); GASTROENTEROLOGY & HEPATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); Hepatoloji; Gastroenteroloji; Hepatology; Gastroenterology; FibroScan; kidney transplant recipients; mafld; DIAGNOSIS; PROVEN; FibroScan; kidney transplant recipients; mafld